A triple-band voltage-controlled oscillator with a triple-resonance resonator. (January 2019) - Jang, Sheng-Lyang; Liu, Yi-You; Juang, Miin-Horng
Abstract: This paper studies the RF property of a 0.18 μm triple-band (TB) oscillator, which is composed of a pair of switching FETs and a triple-resonance resonator. The triple-resonance resonator with three distinct resonant frequencies is made of two shunt dual-resonance LC resonators. MOS varactors with external bias control are used to change the resonant frequencies and the oscillation frequencies. High, middle, low-frequency bands are measured and simulated. At higher supply bias, the frequency tuning range shows two hysteresis loops attributed to the memory effect of varactor capacitance. Low supply operation can be used to suppress the frequency tuning hysteresis loop and the oscillator has good figure of merit.